Analisis Penggunaan Microsoft Excel dalam Pembukuan Keuangan Perusahaan: Sebuah Kajian Literatur (Lembaga Pengembangan Kinerja Dosen, 2025)
Microsoft Excel has become a common tool used in corporate financial bookkeeping, especially for small and medium enterprises (SMEs). This article aims to analyze the use of Microsoft Excel in corporate financial bookkeeping through a literature review from various sources obtained through Google Scholar with the keyword